The Dynamics of E-Government Policy in the Management of Political Party Financial Assistance Funds in Bali Province - Luh MD. Adinda Sukma Prabandari; Nyoman Sri Subawa (Bulletin of Community Engagement, 2026)
This study aimed at exploring the implementation of e-government in the management of political party financial assistance in Bali Province, focusing on its administrative effectiveness, challenges, and supporting factors. A descriptive qualitative research design was employed. Data were collected through semi-structured interviews with six purposively selected informants, observations, and document analysis. The research instruments used were interview guide, observation sheet, and note-taking sheet. The collected data were analysed by using Qualitative Data Analysis consisting of data collection, data reduction, data display, and conclusion drawing, with method and source triangulation used to ensure data trustworthiness. The findings indicated that  1) e-government has gradually transformed conventional administrative practices into a hybrid digital-conventional system, 2) the digital transformation remains incomplete due to differences in human resource capacity, limited system integration, technical problems, and organizational resistance to conventional procedures, and 3) the implementation is supported by government policies and regulations, leadership commitment, ICT infrastructure, technical assistance, political party commitment, and administrative capacity. The study concludes that e-government implementation in political party financial assistance management is progressive but not yet fully transformative. Its effectiveness depends not only on technological availability but also on institutional readiness, organizational adaptation, stakeholder commitment, and human resource capacity. The study highlights the importance of strengthening digital integration and institutional capacity to achieve more sustainable, transparent, accountable, and efficient public financial governance